New Features in the National eAppointment Solution - Kosednar, Hajdi; Stanimirović, Dalibor (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
eAppointment (eNaročanje) is an information system for electronic referrals and scheduling of patients for specialist healthcare services. It includes centralized waiting lists and up-to-date information on waiting times. The system covers more than 2,100 types of healthcare services and allows the review of patients' e-referrals and e-appointments. In 2024, numerous changes and improvements were introduced to eAppointment. The upgrades were implemented in collaboration with the Ministry of Health, the Health Insurance Institute of Slovenia, the eAppointment solution maintainer, the zVEM platform, and software companies maintaining local information systems. These innovations reduce the administrative burden on doctors. Appointment reminders will help decrease patient no-shows, while rescheduling for the longest-waiting patients will reduce the number of patients on waiting lists and shorten waiting times.